Identification of key genes regulating brown adipose tissue thermogenesis in goat kids (Capra hircus) by using weighted gene co-expression network analysis - Li, Minhao; Zhu, Qingjun; Yang, Haili; Hu, Yunyi; Zhao, Le; Zhao, Yongju (Frontiers in Veterinary Science, 2025)
Brown adipose tissue (BAT) is crucial for the maintenance of body temperature in newborn animals through non-shivering thermogenesis (NST). However, which kind key genes involved in the regulation of BAT thermogenesis and the internal regulation mechanism of heat production in goat BAT were still unclear. In this study, we analyzed the perirenal adipose tissue transcriptome of Dazu black goats from 0, 7, 14, 21 and 28 days after birth using weighted gene co-expression network analysis (WGCNA) to identify key genes involved in the thermogenesis of BAT. Genes were classified into 22 co-expression modules by WGCNA. The turquoise module exhibited high gene expression in D0, with generally lower expression in the later dates. This pattern is consistent with the rapid color, morphological, and thermogenic changes observed in perirenal adipose tissue shortly after birth. GO functional annotation revealed that the genes in the turquoise module were significantly enriched in the mitochondrion, mitochondrial protein-containing complex, cytoplasm, and mitochondrial inner membrane. KEGG pathway enrichment analysis indicated that these genes were predominantly enriched in the signaling pathways of oxidative phosphorylation, thermogenesis, and TCA cycle. By combining the gene co-expression network analysis of the turquoise module genes and the differentially expression genes (DEG) analysis, we identified 5 candidate key genes (ACO2, MRPS27, IMMT, MRPL12, and TUFM) involved in regulation of perirenal adipose tissue thermogenesis. This finding offer candidate genes that in the regulation of BAT thermogenesis and body temperature maintenance in goat kids.